Pelatihan Pembuatan Selai Labu Siam Sebagai Upaya Peningkatan Nilai Tambah Wirausaha di Desa Tapak Siring Kecamatan Sukau, Kabupaten Lampung Barat - Ayuningtyas, Salsafira; Sutiana; Haryani, Pipit Dwi; Nathaniela, Desi Maharani; Saputro, Cipto Hadi; Khoirunnisa, Icha; Wirayudha, Rafli; Listiana, Indah (Jurnal Pengabdian dan Pemberdayaan Masyarakat Inovatif, 2023)
Tapak Siring Village, Sukau District, West Lampung Regency, where most of the people work as farmers and one of their agricultural commodities is chayote. The problem faced by this community is limited knowledge in innovating food products to increase sales value, so that chayote is only processed into daily food ingredients, and also used as animal feed. Based on this problem, an activity will be carried out in the form of training on processing chayote-based ingredients into creative and innovative food products, namely making chayote jam. This activity aims to help the community, especially mothers in fostering family welfare in increasing their knowledge and skills in diversifying food products. It was carried out on January 26 and at the TAPAK SIRING 2 KKN residence post. The method used was through the implementation of activities in the form of product manufacturing training. The result of this activity is that the community is able to increase their knowledge and develop their creativity in processing chayote into innovative food products, namely jam.